Antibacterial and Antifungal Activity Test of N-Hexane, Ethyl Acetate, and Ethanol Extracts of Menteng Leaves (Baccaurea racemosa (Reinw.) Mull.Arg.) Against Candida albicans, Staphylococcus aureus, and Escherichia coli - Ika Julianti Tambunan; Yessi Febriani; Yufida Laia; Peronika Tampubolon; Sudewi (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Infectious diseases caused by Staphylococcus aureus, Escherichia coli, and Candida albicans remain a global health problem. Since prolonged use of synthetic drugs can cause side effects and resistance, natural alternatives are needed. Menteng leaves (Baccaurea racemosa) contain alkaloids, flavonoids, saponins, steroids/terpenoids, and tannins, which have potential antimicrobial properties. Objective: This study aimed to determine the antibacterial and antifungal activities of n-hexane, ethyl acetate, and ethanol extracts of menteng leaves against S. aureus, E. coli, and C. albicans. Method: The research was conducted experimentally through sample collection, simplicia preparation, successive maceration extraction, phytochemical screening, and antimicrobial testing using the agar well diffusion method. Results: From 500 g of simplicia, 10.5 g of n-hexane extract, 11.4 g of ethyl acetate extract, and 18 g of ethanol extract were obtained. Phytochemical screening showed that all three extracts contained different secondary metabolites, with the ethanol extract having the most complete profile. The highest antimicrobial activity was observed in the ethanol extract, with inhibition zones of 18.92 mm against S. aureus, 18.35 mm against E. coli, and 19.58 mm against C. albicans at a concentration of 200 mg/mL. Conclusion: These results indicate that the ethanol extract of menteng leaves has strong potential as a natural antibacterial and antifungal agent.